2011
DOI: 10.1002/pssc.201000893
|View full text |Cite
|
Sign up to set email alerts
|

On the reduction of efficiency loss in polar c ‐plane and non‐polar m ‐plane InGaN light emitting diodes

Abstract: We have undertaken a series of experiments in InGaN light emitting diode (LED) structures both on polar (c‐plane) and non‐polar (m‐plane) GaN substrates with and without magnesium doped AlGaN electron blocking layers (EBLs) on the p‐side of the p‐n junction to shed the much needed light on the carrier injection and transport. The LEDs grown on c‐plane bulk GaN substrates without EBL show 40% peak electroluminescence (EL) intensity, while the EL peak intensity of the LEDs grown on m‐plane bulk GaN substrates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Several groups have linked this behaviour directly to the absence of the internal electric fields. From measurements on non-polar LEDs, Ling et al 18 and Li et al 19 assigned the reduction in droop to reduced losses associated with carrier spill over due to the improved carrier confinement. However, an alternative explanation was put forward by Li et al 20 and Chang et al 21 who suggested that droop was reduced because of the improvement in hole distribution amongst the QWs in multiple QW LEDs.…”
mentioning
confidence: 99%
“…Several groups have linked this behaviour directly to the absence of the internal electric fields. From measurements on non-polar LEDs, Ling et al 18 and Li et al 19 assigned the reduction in droop to reduced losses associated with carrier spill over due to the improved carrier confinement. However, an alternative explanation was put forward by Li et al 20 and Chang et al 21 who suggested that droop was reduced because of the improvement in hole distribution amongst the QWs in multiple QW LEDs.…”
mentioning
confidence: 99%
“…8,9,15 In addition, previous reports showed that EBLs mitigate efficiency droop in non-polar devices implying that electron overflow plays an important role even in non-polar InGaN LEDs. 16 Most commercial LEDs are fabricated with the p-top junction oriented along the þc or (0001) direction (p on top of n on a þc oriented substrate). Reversed polarization devices can be achieved using a p-down structure on a Ga-polar substrate (n on top of p on a þc oriented substrate) or a p-up junction on a Àc oriented or N-polar substrate (p on top of n on a Àc oriented substrate).…”
mentioning
confidence: 99%
“…The need to manage piezoelectric polarization in InGaN/GaN superlattices 29 has led to attempting to synthesize devices on substrates with non-polar and semi-polar crystal orientations. 30,31,32,33 However, the output powers at high injection current of these devices currently do not outperform the best devices grown on (0001) planes (c-planes). 14,34, 35 Crutchley et al 36 showed experimentally that there appears to be a linear correlation between the change in internal field and the reduction of the optical effici-FIGURE 5.…”
Section: Iii-n Light Emitting Diodesmentioning
confidence: 99%